Interactive Logic Selected Papers from the 7th Augustus de Morgan Workshop, London - van Benthem, Johan; Gabbay, Dov; Löwe, Benedikt (Texts in Logic and Games, 2008)
Traditionally, logic has dealt with notions of truth and reasoning. In the past several decades, however, research focus in logic has shifted to the vast field of interactive logic - the domain of logic for both communication and interaction. The main applications of this move are logical approaches to games and social software. This collection of papers from the workshop serves as the initial volume in the new series Texts in Logics and Games.